Ambiguity and contradictions in the assistance provided for women who suffer violence - Villela, Wilza Vieira; Vianna, Lucila A. Carneiro; Lima, Lia Fernanda Pereira; Sala, Danila C. Paquier; Vieira, Thais Fernanda; Vieira, Mariana Lima; Oliveira, Eleonora Menicucci de (Saúde e Sociedade, 2011)
This article discusses the assistance provided by healthcare services and public security services for women who suffer violence. It presupposes that the current policies targeted at violence against women expect actions from these two institutions. It is based on the three elements that constitute the practice: the setting, the services flows and the professionals' perceptions about users. Data were extracted from a qualitative study that was carried out in primary healthcare units, emergency services of public hospitals, women's police stations and police departments in a region of the city of São Paulo. Data collection included non-participant observation and interviews with professionals. The results show that the assistance provided for women who suffer violence is marked by ambiguities and contradictions; the work spaces and flows are inappropriate; and the professionals' perceptions are pervaded by gender stereotypes. This suggests the need for practices reconfiguration, with continuing education for professionals as well as changes in work processes.